2012
DOI: 10.1016/j.tibs.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA base excision repair: a mechanism of trinucleotide repeat expansion

Abstract: Expansion of trinucleotide repeat (TNR) sequences in human DNA is considered to be a key factor in the pathogenesis of more than 40 neurodegenerative diseases. TNR expansion occurs during DNA replication and also, as suggested by recent studies, during the repair of DNA lesions produced by oxidative stress. In particular, the oxidized guanine base, 8-oxoG, within sequences containing CAG repeats may induce formation of pro-expansion intermediates through strand slippage during DNA base excision repair (BER). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 74 publications
0
134
0
Order By: Relevance
“…In fact, the results from all studies have shown that TNR instability can be generated during any DNA metabolic pathways that involve formation of single-stranded DNA including replication (104,105), transcription (106), repair (11,12) and recombination (107).…”
Section: Tnr Instability and Dna Repairmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the results from all studies have shown that TNR instability can be generated during any DNA metabolic pathways that involve formation of single-stranded DNA including replication (104,105), transcription (106), repair (11,12) and recombination (107).…”
Section: Tnr Instability and Dna Repairmentioning
confidence: 99%
“…In the human genome, typical non-B form structures arising from (CAG) n /(CTG) n , (CTG) n /(CAG) n , (CGG) n /(CCG) n and (GAA) n /(TTC) n sequence contexts include hairpins, tetraplexes and triplexes (85,86). These DNA secondary structures can cause DNA polymerase pausing and DNA slippage (108,109), replication fork stalling and collapse (86,97,98) Thus, inefficient BER leads to TNR expansion (11). A multi-nucleotide gap generated during BER could also allow the formation of a hairpin on the template strand that may mediate TNR deletion induced by DNA damages.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations